2016
DOI: 10.21776/ub.jtp.2016.017.03.6
|View full text |Cite
|
Sign up to set email alerts
|

Production and Identification of Antimicrobial Compounds from Microalgae Tetraselmis chuii with Ultrasound Assisted Extraction Method (Study Type of Solvent and Total Cycle Extraction)

Abstract: Pada ekosistem air, mikroalga merupakan penghasil alami energi dan senyawa metabolit potensial. Mikroalga ekstraseluler memiliki fungsi sebagai penghambat dan memicu pertumbuhan senyawa. Tetraselmis chuii memiliki komponen bioaktif seperti asam lemak dan ester yang digunakan sebagai agen antibakteri. Antimikroba adalah senyawa yang dapat menghambat pertumbuhan mikroba. Proses ekstraksi dipengaruhi oleh metode ekstraksi, berbagai pelarut, dan kondisi ekstraksi. Tujuan penelitian ini adalah untuk mendapatkan inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
2
0
3
Order By: Relevance
“…High amounts of diacetone alcohol were detected in all tested cyanobacterial species. Maligan et al (2013) reported that Tetraselmis chuii extract using acetone solvent was also contained high amounts of diacetone alcohol (53.617) which is in good agreement with our results. Alcohol groups have a toxic effect on microorganism (Sikkema et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…High amounts of diacetone alcohol were detected in all tested cyanobacterial species. Maligan et al (2013) reported that Tetraselmis chuii extract using acetone solvent was also contained high amounts of diacetone alcohol (53.617) which is in good agreement with our results. Alcohol groups have a toxic effect on microorganism (Sikkema et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Senyawa aktif yang termasuk dalam golongan asam lemak organik pada minyak atsiri daun tembakau Kasturi adalah hexadecanoic acid (5,11% dan 1,56%) dan 17-octadecanoic acid, methyl ester (CAS). Selain itu, senyawa hexadecanoic acid dapat memberikan efek terhadap adanya partisi ion pada lapisan membran sel dari mikroorganisme seperti Candida albicans (Maligan et al, 2016). Respon penghambatan pertumbuhan C. albicans dapat dilihat melalui kurva polinomial (Gambar 4), kurva logaritmik (Gambar 6) dan kurva probit (Gambar 7).…”
Section: Gambar 4 Persentase Penghambatan Minyak Atsiri Daun Tembakau...unclassified
“…Adanya perbedaan waktu pertumbuhan dapat mempengaruhi jumlah koloni C. albicans yang diamati dan terjadi peningkatan pertumbuhan. Selain itu, peningkatan pertumbuhan koloni C. albicans pada waktu 48 jam juga dapat disebabkan dengan karakteristik dinding sel tersebut yang lebih kuat dengan adanya manan (15,2%) dan glukan (47%) yang menyusun dinding sel C. albicans (Maligan et al, 2016).…”
Section: Gambar 4 Persentase Penghambatan Minyak Atsiri Daun Tembakau...unclassified
“…Several studies have reported the use of ultrasound technology for carotenoid recovery from algal biomass using different ultrasound frequencies, from low frequencies of 18–200 kHz to high frequencies of 400–10 MHz [ 15 , 20 ]. However, only a few studies have described the effects of this technology on the antimicrobial activity of the resulting microalgae extracts [ 21 , 22 ]. The novelty of this study is not related to the use of UAE technologies but to their specific application to developing green extraction processes from acidophilic microalgae; extremophilic microalgae are gaining relevance in biotechnology [ 5 , 6 , 10 ], and extraction procedures must be developed which unveil novel active molecules and efficient recovery protocols.…”
Section: Introductionmentioning
confidence: 99%